Cross Sectional Analysis of Adipose Tissue and Fatty Liver Prevalence in association with sugar sweetened beverages consumption. - Nabeela Habib, Muhammad Usman Naeem, Muhammad Ijaz, Madiha Amjad, Muhammad Usman Sheikh, Muhammad Afzal, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To establish cross-sectional association of consumption of Sugar sweetened beverages with adipose tissue (body fat) and risk of developing fatty liver. Methods: A thorough investigation was done by collecting data on sugar sweetened beverages consumption, Body fat and Fatty liver was collected systematically in different public and private hospitals and private clinics of Lahore. For the assessment of adipose tissue in the body, every patient was subjected to the recording of Body Adiposity Index (BAI) using Height and Hip Circumference measurement. Presence of Fatty Liver was determined by screening using Abdominal Ultra-sound. Results: Consuming SSB more than once per day increased the risk of being overweight to 2.64 (p value <0.05) times and risk of being obese to 2.22 times (p value < 0.05). Participants consuming SSB once a day had 9% statistically significant increased risk of getting fatty liver while those consuming more than once per day showed 14% increased risk of developing fatty liver. Conclusion: It is concluded that Sugar sweetened Beverages Consumption is attributed as common risk factor to Adipose tissue accumulation as well as Fatty Liver.